Legal capacity and the prohibition of forced interventions under the Brazilian Inclusion Law: Capacidade civil e a proibição de intervenções forçadas na Lei Brasileira de Inclusão - Adriano Araújo, Luana (Ponto de Vista Jurídico, 2025)
This article examines the persistence of forced interventions in the Brazilian legal framework a decade after the enactment of the Brazilian Inclusion Law (Lei Brasileira de Inclusão – LBI), which aimed at harmonizing national legislation with the Convention on the Rights of Persons with Disabilities (CRPD). Although the LBI formally abolished disability-based civil incapacity, limited guardianship to patrimonial affairs, and prohibited non-consensual medical and institutional interventions, coercive practices remain prevalent in areas such as reproductive regulation and psychiatric treatment. The first section examines the shift from discernment-based incapacity to the recognition of legal capacity, highlighting unresolved tensions between legal capacity and competence to consent. The second section refers to the LBI’s prohibition of forced interventions, in contract to ongoing forms of coercion. It concludes that the transformative potential of the LBI and the CRPD depends on the dismantling of said coercive practices. Keywords: Legal capacity. Disability rights. Forced interventions. RESUMO: Este artigo analisa a manutenção de intervenções forçadas no ordenamento jurídico brasileiro uma década após a promulgação da Lei Brasileira de Inclusão (LBI), que buscou harmonizar a legislação nacional com a Convenção sobre os Direitos das Pessoas com Deficiência (CDPD). Embora a LBI tenha formalmente abolido a incapacidade civil baseada na deficiência, restringindo a curatela a assuntos patrimoniais e proibido intervenções médicas e institucionais sem consentimento, práticas coercitivas continuam recorrentes em áreas como o controle reprodutivo e o tratamento psiquiátrico. A primeira seção examina a transição da incapacidade baseada na categoria “discernimento” para o reconhecimento da capacidade legal, destacando tensões não resolvidas entre capacidade jurídica e competência para consentir. A segunda seção trata da proibição legal de intervenções forçadas, contrastando-a com formas de coerção ainda em curso. Conclui-se que o potencial transformador da LBI e da CDPD depende da eliminação de tais práticas coercitivas. Palavras-chave: Capacidade legal. Direitos das Pessoas com Deficiência. Intervenções Forçadas.